THE USE OF YOUTUBE CHANNEL PRACTICAL PSYCHOLOGY AS MEDIA IN TEACHING VOCABULARY TO SIXTH GRADE STUDENTS OF SD NEGERI BANGKEH KABUPATEN PIDIE - Yuny Jafriany; Siti Mayang; Akmaluddin; Zahraini Zainal (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The purpose of this study is to determine whether or not using the YouTube channel Practical Psychology to help sixth-grade pupils learn vocabulary is helpful. In the instance of the experiment research approach, quantitative research is used in this study. The research's design is a pre-experiment with one group that underwent pre- and post-testing. One class is used in this arrangement, and pre- and post-tests are administered before and after treatment. The purpose of this treatment is to test the effects of a certain treatment. The pupils of SD Negeri Bangkeh's sixth grade during the academic year 2022/2023 make up the study's population. There are 25 pupils in all, all of them were in the same class. Only 25 kids were enrolled in the sixth grade, thus that group was chosen as the sample group for this study. N-Gain Score was used to analyze the data that was obtained. According to the study's findings, the sixth-grade pupils' proficiency with vocabulary can be improved by using the YouTube channel Practical Psychology. This is supported by It is demonstrated by the N-Gain score calculation result, which is 0.58. The use of the Practical Psychology YouTube channel to teach listening skills is sufficient/effective enough.